Treatment for in-stent restenosis: patient-specific decision rather than universal recommendation - Lee, Joo Myung; Park, Jonghanne; Rhee, Tae-Min; Kim, Hyo-Soo (Journal of Thoracic Disease, 2016)
The development of the drug-eluting stent (DES) created a milestone in the field of percutaneous coronary intervention (PCI) by markedly reducing the rates of in-stent restenosis (ISR) compared to the bare metal stent (BMS).